PELAKSANAAN SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU PENDIDIKAN AGAMA ISLAM SMA NEGERI 3 PRABUMULIH TAHUN PELAJARAN 2023/2024 - Pertiwi, Anggi Dwi; Nasor, M; Praja Tuala, Riyuzen (UNISAN JURNAL, 2024)
Supervision activities for school principals at SMA Negeri 3 Prabumulih are carried out in a planned and sustainable manner with the aim of improving teacher performance in learning. Even though teacher performance was good before supervision was held, it was not yet optimal. The problem in this study is to examine the implementation of supervision by the principal and teacher performance in learning at the SMA Negeri 3 Prabumulih Oku Selatan Madrasah. The problem of this research is how is the Implementation of Supervision of the Madrasa Head in Improving the Performance of Islamic Religion Education Teachers at the SMA Negeri 3 Prabumulih Madrasah, Buay Pemaca Oku Selatan District, 2022/2023 Academic Year?. The purpose of this research is to find out the implementation of the supervision of the Madrasa Head in improving teacher performance at the Darul Huda Oku Selatan Madrasah.This type of research is a qualitative research using data collection techniques of observation, interviews and documentation. The data analysis technique uses analysis to improve teacher performance at the Darul Huda Oku Selatan Madrasah.The results of the study can be concluded, first, planning for supervision activities by the principal starting at the beginning of the school year with reference to the subject schedule, planning a supervision program which is then socialized to all subject teachers to be known together so that teachers can understand the duties and responsibilities assigned to them. . Second, the implementation of Principal Supervision in Improving the Performance of Islamic Religious Education Teachers At SMA Negeri 3 Prabumulih Buay Pemaca City District, , principals use individual supervision techniques by involving senior teachers who are considered capable and understand the teaching and learning process. The principal supervises teachers by jointly coaching teachers, conducting individual supervision with class visits, class observations and individual meetings. Third, the follow-up program for the supervision of the principal in the form of general guidance through teacher council meetings. Fourth, the supervision of the principal is considered successful in improving the performance of PAI teachers, because the implementation of the supervision of the principal has been planned, systematic and sustainable.